Keberadaan Qanun Nomor 3 Tahun 2013 tentang Bendera dan Lambang Aceh Ditinjau dari Pembentukan Peraturan Perundang-Undangan: - - Herlin, Herlin (Diktum: Jurnal Ilmu Hukum, 2021)
Based on the provisions of Article 246 paragraph (2) of Law Number 11 the Year 2006 concerning Aceh Government, the design and enactment of Qanun Number 3 of 2013 on the Flag and the Symbol of Aceh, the clarification result of the Ministry of Home Affairs of the Republic of Indonesia is considered contradictory to PP 77/2007 Coat of Arms. The purpose of this research is to know and study the existence of Qanun Number 3 the Year 2013 about Flag and Symbol of Aceh, and to know the implementation of Qanun Number 3 the Year 2013 about Flag and Symbol of Aceh. This research uses normative legal research method that is to study the study of legal documents in the form of legislation, government regulation and qanun as well as to analyze law from normative juridical aspect which means to examine the laws and regulations relevant to the issues in the research.